Container Infrastructure on Laravel to Improve Online Shop - Sucianna Ghadati Rabiha; Achmad Fadhitya Muharram; Fahmi Anwar Kusuma; Hendrawan Sulistya; Eduard Pangestu Wonohardjo; Emny Harna Yossy (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
A laundry business is a business that operates laundry services or similar and is often used by the general public. The development of this business is quite fast, as many consider renting laundry to be more convenient. This rapid increase is inversely proportional to the evolution of companies in using technology as a means of digitizing their businesses. The digitization process can make it easier for business owners to manage, monitor, promote, and receive business reviews. One attempt to overcome this is to develop a web-based laundry management and publishing application using the Laravel framework and container infrastructure, with the aim of making business management and advertising easier for laundry entrepreneurs and customers to choose from to facilitate washing area. This study uses data collection techniques in the form of literature reviews, questionnaires and uses technologies to facilitate the development process such as the Laravel framework, MySQL, Google Maps API, and container and waterfall infrastructure as application development methods. The test technique used is black box. The result of the research is a web-based laundry application that conforms to the eight golden rules, has been tested by laundry owners and customers, and can achieve the research goals.